Desenvolvimento e aplicação de uma metodologia para previsão de vida de eixos de mandris de bobinadeiras de laminação a frio submetidos a danos acumulados por fadiga - Sergio Rolla Guimaraes (2009)
This work presents the development of a methodology to predict the useful life of mandrel shafts from cold rolling coilers, submitted to cumulative damage due to fatigue. The proposed methodology is based on the accumulation of damages due to fatigue on the piece, where theloads chronological history and the mandrel shafts physical and geometric characteristics are introduced in the life prediction model. Miners rule is used to quantify the fatigue damage on the mandrel shaft caused by each processed coil. The main purpose of this work isto propose a methodology to be applied by maintenance as a control tool to estimate the useful life of mandrel shafts submitted to fatigue damage accumulation, based on the load history and on the shafts physical and geometric characteristics. The methodology was initially applied to two experimental cases in order to adjust and check the suitability of themodel. It was observed that the type and load sequence have a significant influence on the result of the accumulated final damage and on the degree of adjustment to the proposed linear model. For cases with loads closer to the fatigue limit of the shafts critical section, it wasobserved a better suitability to the linear model. The application of the methodology was validated in a third case, where the shaft was removed for inspection during its useful life. A feasibility study was also accomplished, as a fourth case, where the achieved benefits aredemonstrated using the methodology, taking into consideration the high contribution margin of flat products and the shutdown involved time. The adoption of this methodology by maintenance sector will enable the calculation of predicted useful life of shafts, serving as a control method that may guide the maintenance actions regarding mandrels shafts.